Families in focus. New perspectives on mothers, fathers and children / Judih Bruce, Cinthia B. Lloyd, Ann Leonard - Bruce, Judith [et..al] (1995)
Family in transition,later marriage and chidbrirth, smaller families and households, increasing proportion of female, headed households; the economics of motherhood, prevalence of nother, supported families, wage, earning and domestic woek, mother´s dual productive duties,mother´cas income, afamily necessity; fathers as parenting partners, factors affecting father, child relationships, continuin the discourse on father, innovative measures; familial risk factors for children, familyy policy, supporting the parent, child link.